Record on Macroscopic Fungi at IPB University Campus Forest : Description and Potential Utilization - Ivan Permana Putra (Indonesian Journal of Science and Education (IJOSE), 2020)
Fungi are ubiquitous and worldwide in distribution. It is estimated that tropical region such as Indonesia has high diversity of macro fungi. Studies on the diversity and potential utilization of macrofungi have gained significance during the recent years in Indonesia. However, information provide in the term of institutional area are still limited, and campus forest is no exception. The aim of this study was to collect information of mushroom diversity at IPB Unversity Campus Forest as inital step to maximize the potential utilization in the future. All mushrooms found were Basidiomycota which dominated by the order of Agaricales. A total of 11 mushroom were identified and described in this study,  namely : Crinipellis sp., Marasmius sp.1, Marasmius sp.2, Termitomyces sp., Cortinarius sp., Coprinellus sp., Pluteus sp., Gymnopus sp., Schizophyllum sp., Lentinus sp.1,and Lentinus sp.2. Some wild macroscopic fungi found to be potentially used as food source, secondary metabolites source, medicine, and also decomposer in sampling site.Keywords: Macro Fungi, Diversity, Potency, IPB University.